Consentimiento estatal al arbitraje del CIADI - Pérez Pacheco, Yaritza (2013)
Arbitration in foreign investment with special attention to the jurisdiction\nof International Centre for the Settlement of Investment Disputes, known as ICSID,\nis part of the International Law of Investment. ICSID was established during the\nWashington Convention of 1965 and has become the natural forum to hear investment\ndisputes between States and nationals of other States. In this context, there have been\ndoubts over various aspects linked to the formation of consent to submit to international\narbitration, including the modalities (contract, laws and treaties), in particular\nthe methods and effects of the manifestation of consent by the host State. It has been\nused in this work the method of case analysis to extract general parameters in this area\nof knowledge. At present, international arbitration is a guarantee offered by the State,\nwhich has generated a climate of greater security for foreign investors in dealing with\nrecipient and investment has encouraged the growth of international trade.